The effect of the Deepwater Horizon oil spill on two ecosystem services in the Northern Gulf of Mexico. (November 2020) - Rohal, Melissa; Ainsworth, Cameron; Lupher, Brach; Montagna, Paul A.; Paris, Claire B.; Perlin, Natalie; Suprenand, Paul Mark; Yoskowitz, David
Abstract: The Deepwater Horizon (DWH) oil spill likely affected ecosystem services in the Gulf of Mexico. To test this hypothesis, we configured a "Ecopath with Ecosim" model and quantified the effects of commercial fisheries and particulate organic carbon (POC) sequestration from 2004 to 2014, encompassing DWH. The yield of five functional groups were used to calculate changes in fishery catch and detritus biomass as a proxy for carbon buried offshore to calculate POC sequestration. The model predicted an estimated loss of 15–16 million per year (−13%) in stone crab fisheries but estimated gains of up to 20 million per year (11%) in the other four groups from 2010 to 2012. Model simulations estimated a loss of 1200 (−0.15%) in the ability of the Northern Gulf of Mexico offshore environment to sequester POC in 2010. The DWH simulation led to an increase in fisheries overall and decrease in POC sequestration ecosystem services in 2010. Highlights: The yield of five functional groups were used to calculate changes in fishery catch. Detritus biomass was used as a proxy for carbon buried offshore to calculate POC sequestration. The DWH simulation led to an increase in fisheries overall and decrease in POC sequestration ecosystem services in 2010. The model predicted an estimated loss of 15–16 million per year in stone crab fisheries but estimated gains of up to 20 million per year in the other groups from 2010 to 2012. Simulations estimated a loss of 1200 in the ability of the offshore environment to sequester POC in 2010.